Quantification of Osseointegration of Plasma-Polymer Coated Titanium Alloyed Implants by means of Microcomputed Tomography versus Histomorphometry. (30th April 2015) - Gabler, Carolin; Zietz, Carmen; Bieck, Richard; Göhler, Rebecca; Lindner, Tobias; Haenle, Maximilian; Finke, Birgit; Meichsner, Jürgen; Testrich, Holger; Nowottnick, Mathias; Frerich, Bernhard; Bader, Rainer
Abstract : A common method to derive both qualitative and quantitative data to evaluate osseointegration of implants is histomorphometry. The present study describes a new image reconstruction algorithm comparing the results of bone-to-implant contact (BIC) evaluated by means of µ CT with histomorphometry data. Custom-made conical titanium alloyed (Ti6Al4V) implants were inserted in the distal tibial bone of female Sprague-Dawley rats. Different surface configurations were examined: Ti6Al4V implants with plasma-polymerized allylamine (PPAAm) coating and plasma-polymerized ethylenediamine (PPEDA) coating as well as implants without surface coating. After six weeks postoperatively, tibiae were explanted and BIC was determined by µ CT (3D) and afterwards by histomorphometry (2D). In comparison to uncoated Ti6Al4V implants demonstrating low BIC of 32.4% (histomorphometry) and 51.3% ( µ CT), PPAAm and PPEDA coated implants showed a nonsignificant increase in BIC (histomorphometry: 45.7% and 53.5% and µ CT: 51.8% and 62.0%, resp.). Mean BIC calculated by µ CT was higher for all surface configurations compared to BIC detected by histomorphometry. Overall, a high correlation coefficient of 0.70 (p < 0.002 ) was found between 3D and 2D quantification of BIC. The μ CT analysis seems to be suitable as a nondestructive and accurate 3D imaging method for the evaluation of the bone-implant interface.